Peningkatan Literasi Deteksi Dini Penyakit melalui Seminar Edukatif bagi Guru dan Karyawan Sekolah di Mutiara Bangsa 3, Jakarta Barat - Ernawati Ernawati; Yohanes Firmansyah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Despite the vital role of early disease detection in preventing complications and minimizing healthcare costs, public awareness regarding this issue remains relatively low. Teachers, as influential figures within educational communities, possess great potential to promote health literacy and recognize early signs of health issues among students and peers. This community engagement program aimed to improve teachers’ and school staff’s knowledge and awareness about the importance of early detection through an educational seminar. The activity took place on July 8, 2025, at Mutiara Bangsa 3 School, located in Jelambar, Grogol Petamburan, and was attended by 97 participants, consisting of teachers and staff members. The seminar lasted 75 minutes and featured Dr. dr. Ernawati, SE., MS., Sp.KKLP as the main speaker. The session was delivered interactively using PowerPoint slides, encouraging active participation and discussion. Observations and feedback collected during and after the event showed an increase in participants’ understanding of the importance of early disease detection, routine health screening, and preventive lifestyle practices. Many participants demonstrated a positive shift in attitude by expressing their intention to undergo regular health check-ups and to share the knowledge gained with students and colleagues. This activity highlights the crucial role of educational institutions in promoting health literacy and acting as platforms for public health promotion. By equipping educators with accurate health information, schools can contribute meaningfully to disease prevention efforts and overall community well-being. The seminar not only enhanced individual awareness but also reinforced the promotive and preventive functions of schools as part of a broader sustainable public health strategy.